Masalah Penetapan Manfaat Jaminan Hari Tua (JHT) Setelah Terbitnya Peraturan Menteri Ketenagakerjaan Nomor 2 Tahun 2022 - Nabilla Putri Febri; Muhammad Abiyyu Arhab (CV Rewang Rencang, 2022)
Old Age Security (JHT) is a social guarantee program that provides cash benefits to participants when reaching retirement age, permanent disability, or death. The provision of JHT benefits is regulated in the National Social Security System Act (SJSN Act), and Government Regulation, and is carried out based on The Minister Of Manpower Regulation No. 2 Of 2022 (Permenaker Nomor 2 Tahun 2022). However, problems arise when there is a conflict regarding the arrangement of JHT benefit payments contained in the regulation. This is evidenced by the difference in arrangements between Article 37 paragraph (3) of the SJSN Act which allows disbursement of JHT funds with a minimum membership of 10 years, while in Article 5 of The Minister Of Manpower Regulation No. 2 Of 2022, the disbursement of JHT funds must wait until the age of 56 years. Therefore, this paper aims to find out the differences in the mechanism of payment of JHT benefits contained in the regulation and legal efforts that can be made related to this issue. The preparation of this article uses normative legal writing methods using a statutory approach (Statute approach) which refers to several relevant laws and regulations.